Uses of Andersen health services utilization framework to determine healthcare utilization for mental health among migrants—a scoping review - Krzyż, Ewa Zuzanna; Antunez Martinez, Oscar Fidel; Lin, Hung-Ru (Frontiers in Public Health, 2023)
Background Migration is a worldwide occurrence that carries significant implications for healthcare systems, and it entails challenges to mental healthcare. The Andersen Behavioral Model is widely used by researchers to determine healthcare service utilization among many populations, including migrants. Our study aimed to explore the ways of using the Andersen Health System Utilization Framework in the literature to discover the utilization of mental healthcare by migrants. Methods This scoping review was based on Arksey and O’Malley’s framework. A comprehensive search was performed across five electronic databases. Results A total of 12 articles from January 1992 to July 2023 identified various versions of the Andersen Behavioral Model to provide an overview of mental health services utilization among migrants. The analysis identified four significant trends in the literature. First, there is a predominant focus on individual characteristics over contextual factors. Second, researchers tend to integrate multiple versions of the Andersen Behavioral Model, and the most is the version from 1995. Third, additional factors specific to migrant populations are incorporated into the model, but the categorization is sometimes unclear. Finally, the majority of studies have used a quantitative approach and are based in North America, suggesting a focus on the significance of mental health in migrant communities in that context. Conclusion In summary, our scoping review calls for further research using the Andersen Behavioral Model to study mental healthcare utilization among migrants. Notable findings include the adaptation of the model to migrant populations, a focus on individual characteristics, a need for more diverse research methods, and the proposal of a new conceptual model to guide research and policy development in this field.